Enzyme Extraction From Pineapple Via Natural Based Aqueous Quaternary Biphasic System - Samsuddin, Muhammad Amir (Universiti Sains Malaysia, 2021)
Enzyme extraction using the deep eutectic solvents has gain interest because of its simplicity and low cost of application. The formation of 4 type of DES in which is ChCl : glucose, ChCl : lactic acid, ChCl : glycerol and ChCl : urea is carried out with different molar ratio. In this study it has been found that the DES formed transparent liquid in room temperature with specific ratio. The molar ratio for ChCl : glucose, ChCl : lactic acid, ChCl : glycerol and ChCl : urea is 2:1, 1:2, 1:2 and 1:2 respectively. With the formation of DES, the formation of ATPS is carried out in order to form the DES-ATPS solvent. The formation ATPS can be achieve between 0.3M of polyethylene glycol and 1.0M of sodium sulfate. The ratio between top phase to bottom phase is 1.3 with the formation time is 41 minutes. The ratio of volume between PEG:Na2SO4:DES is 1:1:0.1. the volume is added in this way to form the DES-ATPS solvent. The calibration curve is created using BSA reagent with uv vis spectrometer reading has the coefficient of determination nearly equal to one. This is for all DES except for glucose since the reading does fit the regression curve. The extraction of bromelain from pineapple is a successful with the top phase has the concentration of protein of 1124.98